Fitting Fixed- and Random-effects Meta-analysis Models Using Structural Equation Modeling with the Sem and Gsem Commands. (October 2015) - Palmer, Tom M.; Sterne, Jonathan A. C.
In this article, we demonstrate how to fit fixed- and random-effects meta-analysis, meta-regression, and multivariate outcome meta-analysis models under the structural equation modeling framework using thesem andgsem commands. While all of these models can be fit using existing user-written commands, formulating the models in the structural equation modeling framework provides deeper insight into how they work. Further, the heterogeneity test for meta-regression and multivariate meta-analysis is readily available from this output.